Serving Constituencies In Business Schools: M.B.A. Program Versus Research Performance - Trieschmann, James S.; Dennis, Alan R.; Northcraft, Gregory B.; Nieme, Albert W. (Academy of Management Journal, 2000)
Business schools strive to meet two goals: knowledge exploration through research and knowledge exploitation through instruction. Our results indicate that research performance (pages published in leading journals) and M.B.A. (master of business administration) program performance (popular business press rankings) are different. Research performance was improved by the number of faculty, the proportion of full professors, the proportion of assistant professors, and editorships. M.B.A. program performance was improved by the budget per faculty member and the proportion of full professors.